2013
DOI: 10.1007/s00330-013-2965-0
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of advanced non-small cell lung cancer (NSCLC) on contrast-enhanced computed tomography: prediction of the response to the first-line chemotherapy

Abstract: TA on CECT images in advanced lung adenocarcinoma provides an independent predictive indicator of response to first-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…Most studies of CT texture analysis have focused on the assessment of neoplasms to determine tumor grade, treatment response, or survival. These studies have reported greater correspondence of heterogeneous tumor texture with higher grade of malignancy and lower overall treatment response and survival (11)(12)(13)(14)35).…”
Section: Musculoskeletal Imaging: Trabecular Ct Texture Analysis In Amentioning
confidence: 99%
“…Most studies of CT texture analysis have focused on the assessment of neoplasms to determine tumor grade, treatment response, or survival. These studies have reported greater correspondence of heterogeneous tumor texture with higher grade of malignancy and lower overall treatment response and survival (11)(12)(13)(14)35).…”
Section: Musculoskeletal Imaging: Trabecular Ct Texture Analysis In Amentioning
confidence: 99%
“…It is impossible to quantitatively validate them against  because  implementation is mainly for PET images and its ROI boundary handling is different from ,  TPS, and . At the time of this writing,  has been used for two substantial projects 11,15 and is currently being used by around 35 researchers from different countries with CT (including contrast-enhanced CT, noncontrast-enhanced CT, cone beam CT, and 4D CT), PET, and MRI images. ROIs have been successfully imported from commercial and research software such as , , MIMvista, , , and .…”
Section: I Testingmentioning
confidence: 99%
“…With these improvements, the overall goal is to better inform and enhance clinical decision making. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] One important advancement in quantitative imaging analysis is the concept of "radiomics." Radiomics is the high-throughput extraction and analysis of quantitative imaging features from medical images.…”
Section: Introductionmentioning
confidence: 99%
“…To face this highly facet topic, a modern approach in medical image analysis is proposed in RADIOMICS [2], [3] authors introduced the extraction from the images of a large number of features and an analysis inspired by genomics analysis and modern Machine Learning (ML) algorithms. Such analysis is now quite common and in many centre studies about prognosis and toxicities have been performed: Ravanelli et al [4] investigate how to predict the effects of the 1st line of chemotherapy in lung cancer treatment by texture analysis; Bayanati et al [5] try to identify, by analysing texture and shape, which features on CT images could predict the state of lymph nodes (benign vs malignant) in lung cancer.…”
Section: Introductionmentioning
confidence: 99%